Primeiro registro de Peckia (Squamatodes) trivittata (Curran) (Diptera: Sarcophagidae) colonizando cadáver humano carbonizado em área de restinga da Bahia, Brasil - Ramos, Ramon Lima; Lopes, Daniele Santos; Pamponet, Fernanda Maria; Thé, Torriceli Souza; Morato, Vanêssa Cristina Gonçalves (EntomoBrasilis, 2018)
Resumo. Apresenta-se o registro de sarcofagídeos colonizando um cadáver carbonizado em uma área de restinga no município de Mata de São João, Bahia, o qual foi encontrado dentro de um recipiente metálico. As larvas coletadas da vítima foram criadas em dieta específica, com temperatura, umidade e fotoperíodo controlados até a fase adulta para possibilitar a identificação taxonômica. Sete espécimes de Peckia trivittata (Curran) emergiram da criação em laboratório. O presente artigo reporta o primeiro registro da espécie P. trivittata em cadáver humano e a primeira ocorrência dessa espécie para o estado da Bahia, Brasil. First record of Peckia (Squamatodes) trivittata (Curran) (Diptera: Sarcophagidae) colonizing carbonized human corpse in restinga area of Bahia, Brazil Abstract. It is presented a record of Sarcophagidae flies colonizing a human carbonized corpse in a restinga area in the municipality of Mata de São João, Bahia, which was found inside a metal container. The larvae collected from the victim were reared in a specific diet, with temperature, humidity and photoperiod controlled until the adult emergence to enable taxonomic identification. Seven adult specimens of Peckia trivittata (Curran) emerged from the laboratory creation. The present article also reports the first record of the species P. trivittata on the human corpse and the first occurrence of this species for Bahia State, Brazil.